Calf care workers' attitudes and personality and their association with calf mortality in large-scale dairy farms - Viidu, Dagni-Alice; Ferguson, Eamonn; Kaart, Tanel; Mõtus, Kerli (Frontiers in Veterinary Science, 2022)
Although calf mortality is a multifactorial problem, little is known about the attitudes and personalities of calf care workers (CCWs) and their association with calf mortality. This study aimed to describe the attitudes, satisfaction, and personality of CCWs in large Estonian dairy herds and to analyze their associations with herd calf mortality. A questionnaire registering CCWs’ attitudes toward their work and calf mortality, personality characteristics, satisfaction and importance of different job-related factors was developed. In total, completed questionnaire data of 161 CCWs from 108 large (>100 cows) Estonian dairy farms were analyzed. Herd-level yearly calf mortality risk (MR) was calculated. Cluster analysis and variance partitioning analysis were applied to reveal the explanatory capacity of CCWs’ attitudes and personalities on calf mortality. The mean yearly herd-level calf MR was 5.4% during the first 21 days of life and 2.7% during 22–90 days of life. Although good calf health and low calf mortality was important for CCWs, dead calves were often seen as inevitable. CCWs were generally doubtful regarding their capacity and available knowledge to influence calf mortality. In high-mortality herds, CCWs were dissatisfied with the calf health situation and farm working equipment and felt that the situation was out of their control. Despite striving, they had less faith that farmworkers could affect the outcomes, such as calf mortality. CCWs’ personality domains explained less than 5% of the variance in the herd’s calf MR, whereas their attitudes and satisfaction explained 20% of the variability in calf MR. The current study revealed the importance of the attitudes and satisfaction of CCWs on calf mortality and highlighted the need to allocate proficient assistance to herds with high calf mortality to mitigate calf health problems and the resulting consequences for CCWs.